The effect of heart of oil palm (Elaeis guineensis) and inner stem of banana stalk (Musa sapientum) on rumen fermentation profiles and kinetics in cattle - Abdul Mahaidin, Rabiatul Adawiyah (2017)
Oil palm (Elaeis guineensis) are known for its uses for both humans and animals. For animals feed, oil palm products include palm kernel cake (PKC), palm kernel expeller (PKE), and other oil palm by product. Many parts from the oil palm tree are been utilized but there are no utilization of the heart of oil palm. Banana (Musa sapientum) tree is known to have a lot of medicinal and nutritive value from all parts of the tree. Previous studies suggest the important of using different parts of banana tree for animal feed. The inner stem of banana stalk are usually been made into food for human rather than for animals. This study was conducted to evaluate the effect of heart of oil palm and inner stem of banana stalk on rumen fermentation profiles in cattle. For inner stem of banana, the nutrient composition are 5.91% of dry matter (DM), 6.43% of ash (OM), 2.86% of crude protein (CP), 10.05% of crude fiber (CF) and -0.33% of ether extract (fat) and have energy 12081 kJ. For heart of oil palm, the nutrient composition are 7.68% of dry matter (DM), 7.15% of ash (OM), 17.59% of crude protein (CP), 8.17% of crude fiber (CF) and 2.87% of ether extract (fat) and have energy 13034.67 kJ. The gas production of inner stem of banana and heart of oil palm were increasing during the 96 hours. There are no significance different in the digestibility of the samples and the control samples.